Penerapan Digital Marketing Untuk Mendukung UMKM Segigit Snack Di Kebumen - Lusiana Rahmawati; Maharani Ikaningtyas (Jurnal Informasi Pengabdian Masyarakat, 2023)
This article discusses the application of digital marketing as a strategy used to support the growth of Segigit Snack Micro, Small and Medium Enterprises (MSMEs) in Kebumen. Using the right digital marketing strategies, such as content marketing, search engine optimization (SEO), online advertising, and social media, can help Segigit Snack reach its target audience in a more measurable and effective way. This study uses a qualitative research method with the aim of analyzing the application of digital marketing in supporting the Segigit Snack UMKM in Kebumen. The results of the study show that through the application of digital marketing, the Segigit Snack UMKM has succeeded in optimizing the potential of digital technology in marketing its products